Caracterização de plasmas frios por espectroscopia óptica de emissão - Alves, Douglas Pereira (2019)
Although little known outside and even within the academic community, plasma, considered the fourth state of matter, is the most abundant state in the known universe. Plasma is defined as an electrically neutral medium containing neutral species and electrically charged species, such as electrons, positive ions, and negative ions that exhibit collective behavior. Plasmas can be both naturally found and produced in the laboratory. Artificial plasmas can be generated in a wide range of pressure and temperature and have the most diverse applications. In particular, cold plasma at atmospheric pressure has been widely used in biomedical applications. Considering the potential of plasmas application, this work aimed at characterizing the cold plasma at atmospheric pressure produced by a Dielectric Barrier Discharge (DBD) reactor. Through optical emission spectroscopy (EOE), a noninvasive technique of characterization of plasmas, where what is measured is the electromagnetic radiation emitted by the medium, the main physical properties of the plasma were inferred. These are the electron density, the gas temperature and the electronic excitation temperature. In addition, a study was carried out on the macroscopic neutrality of plasma loading, Debye's length, plasma parameter and plasma frequency, which are necessary for the definition of plasma. These parameters were obtained from a high resolution monochromator for different values of power and frequency applied to the plasma generator device, obtaining quite satisfactory results and in agreement with the literature.